An Investigation of the Fatigue and Fracture Properties of Selected Hull Plate Samples from the Coast Guard Cutter Staten Island. - James,Lee A. (1969)
The fracture toughness, fatigue crack propagation behavior, and tensile properties were evaluated for six selected hull plate samples at the icebreaker operating temperatures of +28F and -30F. In addition, the nil-ductility transition temperature, chemical composition, average grain size and susceptibility to delayed fracture were investigated. It was found that, in general, the static fracture toughness was reasonably high, and that plane-strain 'validity' could not be achieved at the temperatures of interest with the specimen thicknesses provided. One plate did exhibit a somewhat lower touchness, but the reasons for this were not readily apparent and were beyond the immediate scope of this work. The tensile properties and NDT appear to be reasonable for this grade of steel, and the material exhibited little or no tendency for sub-critical cracking under a sustained load in an aggressive environment. (Author)